The Implementation of the Amtsilati Method in Teaching Reading Skills for Eighth-Grade Students at State Junior High School 13 Jakarta - Ainurridho; Zainal Muttaqin; Raswan (INTIFA: Journal of Education and Language, 2026)
This study aims to determine the effect of implementing the Amsilati method in Arabic language learning on students’ Arabic text reading skills. This research was conducted at SMPN 13 Jakarta, focusing on 30 eighth grade students. The research method used was development research consisting of three stages: pre-stage, stage I, and stage II, with data collection in the form of test results. Based on the results, the study concluded that: first, the application of the Amsilati method in Arabic language learning is generally similar to other teaching methods, but places greater emphasis on student participation in class, particularly in reading Arabic texts. Furthermore, this method focuses on students’ vocabulary and pronunciation mastery, accuracy of wording, and adherence to Arabic grammar rules. Second, the application of the Amsilati method in Arabic language learning for eighth-grade students at SMPN 13 Jakarta resulted in improved Arabic text reading skills, as seen in the improvement in student learning outcomes from the pre-stage to the second stage. Students achieved a total score of 1875 in the pre-stage, with an average score of 62,5. In the first stage, the total score reached 2095 with an average score of 69,8. Meanwhile, the second stage showed a satisfactory increase, with a total score of 2425 with an average score of 80,8.